THE ROLE OF POSYANDU CADRES IN EFFORTS TO IMPROVE THE NUTRITIONAL STATUS OF TODDLERS IN SUKA MAKMUR VILLAGE, PATILANGGIO DISTRICT - Ripanwati Aridi Ti Ripan; Titin Dunggio; Novian S. Hadi (LPPM Universitas Bina Mandiri Gorontalo, 2021)
THE ROLE OF POSYANDU CADRES IN EFFORTS TO IMPROVE THE NUTRITIONAL STATUS OF TODDLERS IN SUKA MAKMUR VILLAGE, PATILANGGIO DISTRICT Ripanwati Aridi1), Titin Dunggio2), Novian S. Hadi3) 1.2.3)University Of Bina Mandiri Gorontalo, Gorontalo E-Mail: Aridiripanwati@gmail.com ABSTRACT The Integrated Health Post is a community role that is managed by cadres, generally who manages the Posyandu in their respective regions voluntarily. The success of Posyandu can be seen from the maternal mortality rate, infant mortality rate, and under-five mortality rate. Posyandu's specific goal is to increase community participation in the implementation of basic health efforts (primary health care), increase the role of cross-sector, and increase the reach of basic health services. The purpose of this study was to find out the role of Posyandu cadres in improving the nutritional status of toddlers in Suka Makmur Village, Patilanggio District. This research was conducted in Suka Makmur Village, Patilanggio District. The method in this study is quantitative using a cross-sectional approach with a point time approach design. The population in this study was mothers who have children aged 1 to 5 years in Suka Makmur Village, Patilanggio District. The sampling technique was taken by total sampling. The results of the study about the role of cadres in Suka Makmur Village, Patilanggio District, the best roles were 25 people (83.3%). The increase in the nutritional status of toddlers in Suka Makmur Village, Patilanggio District, the most with good nutritional status was 26 respondents (86.7%). The results of statistical tests with Fisher's Exact Test correction obtained p-value = 0.048 <á (0.05), thus there is a significant relationship between the role of Posyandu cadres in efforts to improve the nutritional status of toddlers in Suka Makmur Village, Patilanggio District. Keyword: The Role of Cadres, improved Nutritional Status, Toddle INTRODUCTION Posyandu is a Community Based Health Efforts (UKBM) which is managed, by, for, and with the community to empower the community and provide facilities for the community in obtaining basic health services. The Integrated Health Post is a community role that is managed by cadres, generally, these cadres manage posyandu in their respective areas voluntarily [1]. If the Posyandu is programmed thoroughly the problems of malnutrition in children under five, malnutrition, edema, and other health problems related to the health of mothers and children will be easily avoided because remembering that Posyandu is also one of the places for public health services that directly interact with the community. The Success of Posyandu can be seen from the maternal mortality rate, infant mortality rate, under-five mortality rate, and also coverage of other Posyandu programs such as immunization [2]. RPJMN policy direction for health 2020-2024 Improves health services towards universal health coverage, especially strengthening primary health care by encouraging increased promotional and preventive efforts, supported by innovation and the use of technology. RPJMN Strategy 2020-2024 to Improving maternal and child health, family planning, and reproductive health, accelerating community nutrition improvement, increased disease control, strengthening the Healthy Living Community Movement (Germas), Strengthening Health Systems, Drug and Food Control. Ministry of Health Strategic (2020-2024) Increasing quality universal health coverage, Improving public health status through a life cycle approach, increasing the culture of healthy living people through community empowerment and health mainstreaming, increased disease prevention and control and management of public health emergencies, increased health resources, improved good governance [3]. Village Community Health Development (PKMD) is an activity carried out by the community, from the community, and for the community. One of the operational forms of community participation or UKBM (community-based health efforts) namely with the posyandu. Posyandu is one of the means in health service efforts carried out by, from, and with the community, to empower the community and provide facilities for the community to obtain maternal and child health, which is the main objective of posyandu. Posyandu's specific goal is to increase community participation in the implementation of primary health care, increasing the role across sectors, and increasing the reach of basic health services [4]. Posyandu is held for the benefit of the community so that the community itself is actively involved in forming, organizing, and making the best use of posyandu. Community participation is needed in utilizing posyandu. In carrying out their duties, previous health cadres will be given the training to support the smooth implementation of activities to improve the nutritional status of children under five [5]. Nationally, the nutritional status of children in various regions in Indonesia is still a problem. The amount of people with malnutrition in the world reaches 104 million children, and malnutrition is the cause of one-third of all causes of child deaths worldwide. Indonesia is among a group of 36 countries in the world that contribute 90% of the world's nutritional problems [6]. Cadres are the central point in implementing posyandu activities. It is hoped that participation and activeness will be able to drive community participation. However, the presence of cadres is relatively unstable because their participation is voluntary, so there is no guarantee that they will continue to carry out their functions properly as expected. If there are family interests or other interests, the posyandu will be abandoned [7]. In 2017, the total of Posyandu in Indonesia was 291,447 but only 164,487 were active with the percentage of active Posyandu 56.57% [8]. In Gorontalo Province in 2017, the highest proportion of Posyandu was Posyandu Madya 48.5%, then Posyandu Purnama 39%, Posyandu Pratama 10.7%, and Posyandu with Independent strata only 1.9%. According to data from the health office of Gorontalo Province, in 2017 the highest of posyandu was in the Gorontalo Regency area, namely 442 posyandu and the least in the Gorontalo City is 128 posyandu [9]. The development of posyandu in Gorontalo Province aims to provide services to the community, especially improving the nutritional status of children under five. Based on data from the Health Office of Gorontalo Provincial. The results of nutritional surveillance through a survey of monitoring nutritional status (PSG) in 2015 in all areas of Gorontalo province involving the Poltekes of the Ministry of Health found that the prevalence of underweight/malnutrition in Gorontalo province is 24.4%, consisting of 18.8% malnourished toddlers and 5.6% malnutrition. Then the prevalence of stunting / short and very short was 36.5% consisting of 22.4% short and very short toddlers and 14.1%. The prevalence of wasting / thin and very thin children was 13.4% consisting of thin children 9.0% and 4.4% very thin. In 2015 the number of cases of malnutrition in Pohuwato Regency reached 105 cases, in 2016 it decreased to 57 cases and in 2017 totaled 57 cases of malnutrition, this shows that there is still a lack of health services provided by health workers and the role of cadres, especially in improving the nutritional status of children under five [9]. From the results of observations in the work area of Puskesmas Patilanggio, there are 21 posyandu with 30 cadres active in implementing posyandu. Although all of them are active, their roles are still not optimal. There are those whose participation is good and those that are lacking. From 30 cadres, it was found that 60% of their roles were motivators, 70% were administrators, and 60% were educators. After the researcher saw the implementation of posyandu activities carried out by cadres based on the implementation of the Vtable system, it did not implement properly. The implementation is limited to table II (weighing) and table III (recording in KMS). The counseling that should be provided by cadres is, in fact, in the field most cadres are still very dependent on health workers. Cadres only weigh children under five and if there is a scale that is less or more, cadres do not provide health education to mothers who bring a toddler. From the results of interviews conducted by researchers with 5 cadres, 2 cadres said that besides being active in implementing the posyandu, the cadres also do house visits to invite mothers with toddlers to come to the posyandu and take time to discuss with mothers who the house is close to each other. Meanwhile, 3 cadres said that their activities were limited to implementing posyandu. Based on the monthly reports of Puskesmas Patillanggio, in March 2020 the total of all toddlers was 120 people, with 1 person with malnutrition status, 23 people deficient nutrition, 1 person over nutrition, and 95 good nutrition. Meanwhile, in the Sukamakmur village in April 2020 the total of all toddlers was 167 people, with a malnutrition status of 15 people, over-nutrition 2 people, and good nutrition 143 people. The background above encourages researchers to research “The Role of Posyandu Cadres in Improving the Nutritional Status of Toddlers in Suka Makmur Village, Patilanggio District. RESEARCH METHODS This type of research is quantitative using a cross-sectional approach with a point time approach design. This research was conducted from June 2020 to August 2020. The location of this research was in Suka Makmur Village, Patillanggio District. The population in this research was mothers who have children aged 1 to 5 years in Suka Makmur village, Patilanggio district, with a total of 167 mothers of children under five. The sampling of this research using the Slovin formula, where the results obtained that the number of samples of 30 mothers who have toddlers 1 - 5 years old adjusted to the number of samples (cadres). Samples were taken by random sampling. The research analysis used univariate and bivariate analysis, where the bivariate analysis used the chi-square statistical test. RESEARCH RESULTS Univariate Analysis Age distribution of respondents Table 1. Distribusi umur responden Mother's age N % 20 - 25 Years 11 36,7 26 – 30 Years 7 23,3 31 – 35 Years 6 20,0 > 36 Years 6 20,0 Jumlah 30 100,0 Source: Processed data (2020) Based on table 1 above, it can be seen that it shows that from 30 respondents (100%), the most respondents were aged 20-25 years as much as 11 people (36.7%). Distribution of respondents' education Table. 2 Distribution of respondents' education Education N % SD SMP SMA Diploma/Sarjana 19 6 3 2 63,3 20,0 10,0 6,7 Total 30 100,0 Source: Processed data (2020) Based on table 2 above, it can be seen that from the 30 respondents (100%), most of them had primary school education as much as 19 respondents (63.3%). Distribution of respondents' work Table 3. Distribution of respondents' work Pekerjaan N % Housewife Entrepreneur PNS 28 1 1 93,3 3,3 3,3 Total 30 100,0 Source: Processed data (2020) Based on table 3 above, it can be seen that from the 30 respondents (100%) the most respondents have IRT jobs totaling 28 people (93.3%). Child sex distribution Table 4. Child sex distribution Jenis kelamin N % Man Woman 11 19 36,7 63,3 Total 30 100,0 Source: Processed data (2020) Based on table 4 above, it can be seen that from the 30 respondents (100%), most respondents were female, as much as 19 people (63.3%). Age distribution of children under five Table 5. Age distribution of children under five Toddler’e Age N % 12 – 18 Month 19 – 26 Month 27 – 43 Month 51 – 60 Month 8 7 10 5 26,6 23,3 33,5 16,6 Total 30 100,0 Source: Processed data (2020) Based on table 5 above, it can be seen that from the 30 respondents (100%), most respondents were aged 27 - 43 months, totaling 10 people (33.5%). Distribution of cadre roles Table 6. Distribution of cadre roles Cadres’ Role N % Poor Good 5 25 16,7 83,3 Total 30 100,0 Source: Processed data (2020) Based on table 6 above, it can be seen that from the 30 respondents (100%), most respondents had a good role as many as 25 people (83.3%). Distribution of Nutritional Status Table 7. Distribution of Nutritional Status Nutrition Status N % Good Poor Fat 26 3 1 86,7 10,0 3,3 Total 30 100,0 Source: Processed data (2020) Based on table 7 above, it can be seen that from the 30 respondents (100%), most respondents with good nutritional status were 26 respondents (86.7%). Bivariate Analysis Table 8. The relationship between cadres of posyandu cadres and nutritional status of toddler Cadres’ Roler Nutrition Status Total Sig. Good Poor Fat Poor Good 3 (10,0%) 23 (76,7%) 1 (3,3%) 2 (6,7%) 1 (3,3%) 0 (0%) 5 (16,7%) 25 (83,3%) p= 0,048 Total 26 (86,7%) 3 (10,0%) 1 (3,3%) 30 (100,0%) Source: Processed data (2020) The results of statistical analysis using the chi-square test at the level of significance á = 0.05 or the confidence interval p <0.05. The results of statistical tests with the Fisher's Exact Test correction obtained p value = 0.048 <á (0.05), thus it can be said that there is a relationship between the role of Posyandu cadres in improving the nutritional status of toddlers in Suka Makmur Village, Patilanggio District. DISCUSSION The Role of Cadre Based on the results of this research, according to the data obtained, it shows that most of the roles of cadres in Suka Makmur Village have a good role, as much as 25 people (83.3%). The results of this research are in line with research conducted by Onthonhie in Sangihe, whose research results found that most of the cadres (86.9%) had carried out their duties well as cadres in carrying out posyandu activities both as motivators, administrators, and educators [10]. The role of cadres is very important because cadres are responsible for implementing the posyandu program. If the cadres are not active, the implementation of posyandu will also not run smoothly and as a result, the nutritional status of infants and toddlers (under five years old) cannot be detected early clearly [11]. The role of cadres as a motivator can improve the quality of Posyandu, especially in handling health problems. Cadres play a role in implementing posyandu activities and mobilizing maternal activity in posyandu activities. Cadres as implementers at posyandu are tasked with filling in the KMS for toddlers. The completeness and correctness of filling in KMS are very important as information on the status of toddler growth and development. If the role of cadres is lacking, monitoring of toddler growth and development will increase [12]. The role of cadres as educators in providing maximum understanding to mothers of toddlers is very much needed for the progress of children's development and nutritional status. The role of cadres as educators, among others, can explain the KMS data for each toddler or the condition of the child based on the weight gain data depicted in the KMS graph, hold group discussion activities with mothers whose houses are close together, and home visit activities [12]. Nutritional status of children under five Based on the results of this research, according to the data obtained, it shows that most of the nutritional status of a toddler in Suka Makmur Village has a good nutritional status of as many as 26 people (86.7%). The factors that influence the nutritional status of a toddler in Suka Makmur village are in terms of good health services and the role of cadres in increasing education of food consumption for toddlers. The results of this research are in line with the research conducted by Onthonie, most of the results (85.2%) had a good nutritional status [10]. The problem of poor nutrition is caused by various causes in children, namely the result of the consumption of bad food so that the energy entering and leaving is not balanced. The body needs good food choices so that nutritional needs are met and the body functions properly [13]. Lack of knowledge of mothers about nutrition results in low spending, food and quality budgets, as well as less food diversity, besides the ability of mothers to apply information about nutrition in their daily life [14]. Nutrition activities in posyandu are one of the main activities and are generally a priority in the implementation of Posyandu activities and are carried out by cadres [15]. The relationship between the role of cadres on the nutritional status of toddler The results of this research indicate that there is a relationship between the role of posyandu cadres in improving the nutritional status of a toddler. This research is in line with the research conducted by Purwanti et al, which states that there is a relationship between the role of cadres and the nutritional status of children under five [16]. Fitriah's research also states that there is a relationship between the role of cadres and the nutritional status of children under five [17]. The duties of cadres in activities at the posyandu are to conduct early detection of abnormalities in under-fives weight, providing additional food, and how to prevent diarrhea in a toddler. Posyandu cadres are health providers that are close to the targeted posyandu activities. The frequency of meeting with cadres is more frequent than other health workers. Therefore, cadres must be active in various activities, not only in implementation but also in management matters such as planning activities, recording, and reporting of cadre meetings [15]. The role of cadres can help the community in reducing the number of malnutrition, besides, role cadres also help in reducing maternal and toddler mortality rates, by utilizing the expertise and other supporting facilities related to improving the nutritional status of a toddler, so it can be concluded that the role of cadres affects the nutritional status of a toddler, If the role of cadres is higher, the rate of reduction of malnutrition among toddler also high [16]. Based on the results of the research above, the researchers assumed that the role of cadres would be better in carrying out their roles in posyandu activities and helping health workers because cadres had the duties and responsibilities to help improve the nutritional health of toddler. Thereby, the role of a good cadre can affect the nutritional status of children where the better the role of the cadres, the higher rate of good nutrition in toddler and can improve the quality of posyandu, especially in handling toddler health problems so that malnutrition can be resolved quickly through prevention and rapid handling. Besides, the role of good cadres tends to motivate mothers of toddlers to always pay attention to things that can improve the nutrition of their children and motivate mothers to routinely bring toddlers to posyandu to monitor their health. In this research using anthropometric indicators of weight/height because height can provide an overview of the growth function seen from the thin and short stature and height is also very good for seeing past nutritional conditions, especially those related to low birth weight and underweight conditions and nutrition in toddlerhood. Height is expressed in the form of Index TB / U (height for age), or also index weight/height (weight for height) is rarely done because changes in height are slow and usually only done once a year. CONCLUSION The role of cadres in Suka Makmur Village, Patilanggio District is mostly cadres who have a good role. The nutritional status of toddlers in Suka Makmur Village, Patilanggio District has increased with good nutritional status. There is a significant relationship between the role of Posyandu cadres in efforts to improve nutritional status, the better the role of cadres, the better the reduction in malnutrition in a toddler in Suka Makmur village, Patilanggio district. Therefore, it is hoped that cadres will further improve their knowledge and skills by attending regular meetings at every meeting held by the Puskesmas, to further improve themselves in participating actively in posyandu programs. REFERENCES [1] Kemenkes RI. 2012 Pusat Promosi Kesehatan Tahun 2012 tentang Buku Saku Posyandu. [2] Adisasmito W, 2016. Sistem Kesehatan. [3] Kemenkes RI. 2020. Rencana Strategis Kementerian Kesehatan Tahun 2020 - 2024. Jakarta [4] Kemenkes RI. 2013. Laporan Akuntabilitas Kinerja Kementerian Kesehatan. Jakarta. [5] Depkes RI. 2012. Buku Paket Pelatihan Kader Kesehatan. Jakarta. [6] World Health Organization. The Global Burden Of Disease : Geneva: WHO Library. [7] Syafei, A. 2010. Faktor – Faktor Yang Berhubungan Dengan Partisipasi Kader Dalam Kegiatan Gizi Posyandu Di Kelurahan Rengas Kecamatan Ciputat Timur Kota Tangerang Selatan. Jakarta: Universitas Islam Negeri Syarif Hidayatullah [8] Kemenkes RI. 2018. Data dan Informasi Profil Kesehatan Indonesia 2017. Jakarta [9] Dinas Kesehatan Provinsi Gorontalo. 2017. Profil Kesehatan Provinsi Gorontalo. [10] Ontonhie. 2014. Hubungan Peran Serta Kader Posyandu dengan Status Gizi Balita di Wilayah Kerja Puskesmas Manganitu Kabupaten Kepulauan Sangihe. E-Journal Keperawatan. Program Studi Ilmu keperawatan Fakultas Kedokteran Universitas Samratulangi. [11] Isaura, V. 2011. Faktor – Faktor Yang Berhubungan Dengan Kinerja Kader Posyandu Di Wilayah Kerja Puskesmas Tarusan Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan. Padang: Universitas Andalas [12] Anondo. 2007. Kualitas Kader Rendah, Peran Posyandu Melemah [13] Almatsier. 2009. Prinsip Dasar Ilumu Gizi. Jakarta. [14] Ernawati A., 2006. Hubungan Faktor Sosial Ekonomi, Higiene Sanitasi Lingkungan, Tingkat Konsumsi dan Infeksi dengan Status Gizi Anak Usia 2-5 tahun di Kabupaten Semarang Tahun 2003. Tesis. Universitas Diponegoro. [15] Wahyutomo, A. H. 2010. Hubungan Karakteristik Dan Peran Kader Posyandu Dengan Pemantauan Tumbuh Kembang Balita Di Puskesmas Kalitidu-Bojonegoro. Surakarta: Universitas Sebelas Maret [16] Purwanti, D., Pajeriaty., & Rasyid, A. 2014. Faktor Yang Berhubungan Dengan Status Gizi Balita Di Wilayah Kerja Puskesmas Madello Kabupaten Barru. Jurnal Ilmiah Kesehatan Diagnosis Volume 5 Nomor 1 [17] Fitriah, R. 2012. Faktor – Faktor Yang Berhubungan Dengan Peningkatan Gizi Balita Di Wilayah Kerja Puskesmas Dasan Cermen Kecamatan Sandubaya. Mataram: Politeknik Kesehatan.